Rat liver nuclear envelope insulin binding and its effects on endogenous protein kinases - Sabbatini, G P; Sabbatini, G P (Department of Molecular and Cell Biology, 2017)
The postulated model for the insulin - stimulated induction of mRNA efflux (Purrello et al., 1983) is based on the demonstrated binding of insulin to intracellular membrane structures (see chapter 2, section 2.2.1), and the in vitro effect of insulin on nuclear envelope phosphorylation, NTPase activity, and mRNA efflux (see chapter 5, section 5.1). These independent observations have led to the development of a model for the direct induction by insulin, at the level of the nucleus, of mRNA efflux (figure 1.1). However, the specific intracellular insulin binding has been inf erred from kinetic or morphological studies which have not identified a discrete membrane - bound polypeptide(s) as an insulin docking molecule in situ (Goldfine, 1981). Also, the stimulation of NTPase activity has only been established by monitoring the level of general ATP hydrolysis of nuclear envelope fractions in the presence and absence of insulin (Purrello et al., 1983). The scope of this thesis has been to further the understanding of this mechanism by attempting to a) unequivocally identify a specific nuclear envelope - associated insulin docking polypeptide in situ and b) to demonstrate that insulin directly affects the ATP - binding of nuclear envelope ATP - binding proteins. The latter would demonstrate a primary effect of insulin i.e. the modulation of the ATP - binding capacity of identified NTPases / protein kinases (or their release from some inactive storage form), and not a general phenomenon such as elevated ATP.